Self education and the production of indigenous children in the Northwest Amazon (Brazil) - Cácia Oenning da Silva, Rita de (2015)
Supported by ethnographic documentation, by the anthropological literature and by data collected in the field, this article relates the process by which indigenous peoples in the northwest Amazon learn and teach children with the rich dialogue about the production of persons. The techniques and the meaning of «producing people» are transmitted in day to day life, in the interaction between generations, and in the narratives of specialists and family members (especially grandparents). At the same time, this process is intertwined with ritual and mythic knowledge transmission, which is, if not always explicit, always present in the indigenous groups of the region. Children also play active roles in this process of formation and self- formation; in this article, I lay out this social agency my means of a careful description of the day in the life of children in the multiethnic village of Tabocal do uneiuxi, santa Isabel do Rio negro. In this narrative, I point of the ways that children are agents in their own education and self-production, emphasizing their protagonism in the process of «producing people», as they incorporate and transform knowledge.